46 Financial incentives in breast cancer screening: the urgent need to shift from incentivising uptake to promoting active, informed choice through the provision of evidence-based decision aids. (8th June 2022) - Colleoni, Mirela; Bartholomew, Theodore; Schmidt, Harald
Abstract : A patient, a doctor and an ethicist provide a combined viewpoint on the ethically problematic practices in France, UK and US of providing financial incentives to women and healthcare providers to increase mammography screening. They call for urgent reconsideration of policies that incentivize mammography, advocating instead for supporting women by encouraging the use of evidence-based decision aids. Breast cancer screening is controversial and the harms-benefits balance has long been debated. A major harm of screening is overdiagnosis, defined as 'the detection of cancers on screening which would not have become clinically apparent in [a] woman's lifetime in the absence of screening'. The physical and mental harms associated with overtreatment, false-positives, false-negatives, and biopsies are well documented. Financial incentives to women and providers to raise participation rates in breast cancer screening are increasingly being proposed. In France, incentives to providers exist in the form of pay-for-performance bonuses, despite acknowledgement that their use is controversial. In order to further increase participation rates, new measures have been adopted in March 2021. One is to experiment with financial incentives for women and to possibly cover their direct non-medical expenses of screening. This new incentive measure is part of the roadmap for the next 5 years of the decennial Cancer Plan starting in 2021. In the US, incentives for women are already in place. Many private health insurance companies offer in-kind items and various other financial incentives. Incentives are also offered to women in government sponsored programs in the form of financial rewards (for opting in) or penalties (for opting out). On the provider side, breast cancer screening is one of the most common indicators included in pay-for-performance programs. In the UK, although no incentives are currently used it has been suggested by the chair of the Independent Review of Adult Screening Programs that providers should receive financial incentives to increase participation in breast cancer screening. Financial incentives in breast cancer screening are controversial because they raise a number of ethical issues. The risk for women is that informed consent may be compromised, the decision-making process may be unduly influenced, and women may make decisions that they will regret and would not have made in the absence of incentives. Offering providers financial incentives to screen more women may compromise their ability to provide objective information about the harms and benefits of screening. Instead of providing financial incentives to either women or providers to increase uptake, authorities should ensure that women are adequately informed. The decision to screen or not, should be facilitated by the availability of evidence-based and impartial information, written by an independent authorship. Decision support tools should be made available to help women integrate this information with their own preferences, values, and individual risk profile. Further, breast cancer screening targets should be abolished as they risk raising conflicts of interest for providers in facilitating preference-sensitive decisions.